Study on strength, durability and transport properties of cementitious systems admixed with sodium nitrite based corrosion inhibitor - Ahamed, S. Shafeer; Mohammed, M.S. Haji Sheik; Sridhar, R.; Roopa, V. (Journal of Structural Engineering, 2024)
This experimental investigation analyses the strength, durability and transport properties of cementitious systems admixed with sodium nitrite based corrosion inhibitor. The influence of inhibitor incorporation on workability, strength (compression, flexure and splitting tensile strength), durability (resistance to rapid chloride penetration (RCPT), accelerated corrosion (ACT)) and transport mechanism (water absorption and sorptivity) of cement concrete and cement mortar were assessed. In addition, morphology studies were also conducted through SEM. The concrete of grade M25 and cement mortar of mix ratio 1:3 were adopted. The workability of cement concrete and mortar was maintained similar, irrespective of inhibitor addition at 1%, 2% and 5% by weight of binder (bwob). It is found that the addition of inhibitor does not affect the setting time guidelines proposed by Indian standards. There is a reduction in water-cement ratio due to incorporation of inhibitor in concrete / mortar at higher dosages (2% and 5% bwob). Appreciable to significant increase in compression, flexural and splitting tensile strength for Inhibitor Admixed Concrete (IAC) as compared to control concrete, irrespective of dosage addition. RCPT test results indicate the performance grade of control and inhibitor admixed concrete as IAC5%> IAC2%> IAC1%> CC. In ACT, the performance factor was 1.3 - 1.9 for inhibitor admixed mortar when compared with control mortar. Inhibitor Admixed Mortar (IAM) also exhibits appreciable reduction in pore formation and water absorption. The SEM image analysis conducted on 2% IAM, revealed an improved microstructure and cement hydrate formation. The improved strength and durability performance of inhibitor admixed concrete / mortar may be due to (i) enhanced passivation layer on steel surface, (ii) action of chloride repulsion mechanism (iii) reduction in water-cement ratio for similar workability and (iv) improved microstructure exhibited by the ingredients of corrosion inhibitor.